Uma nova abordagem no desenvolvimento de potentes quinonas bioativas contendo dois centros redox: síntese e aspectos mecanísticos - Eduardo Henrique Guimarães da Cruz (2017)
Cytotoxic activity of lapachol derivatives against tumor cells is known and has been studied by the scientific community since the last century. In order to develop a new strategy to improve this bioactivity, turning these substances more cytotoxic against tumor cells and less aggressive against normal cells, new 1,2,3-triazolic naphthoquinone compounds were synthesized, by coupling the naphthoquinone part to organochalcogen groups. The synthetic procedure was planned to engage a ROS generator group to a ROS user group that could use this reactive species in a manner similar to that performed by theenzyme glutathione peroxidase, but without the specificity of this enzyme, leading to deleterious results for the tumor cell. These compounds were evaluated against six different cancer cell lines (HL-60, HCT-116, PC3, SF295, MDA-MB-435 e OVCAR-8) and three normal cell lines (V79, L-929 e PBMC). Most of these compounds showed high cytotoxicity against cancer cell lines (IC50 < 2 M), some of them even more active thandoxorubicine (positive control) and showed a good selectivity index against normal cell lines. Also the ability of two of these triazoles to react with glutathione in the presence of the reactive oxygen species H2O2, compared to medicine drug ebselen was analyzed. Theresults were positive, presenting that these compounds are able to use this reactive species of oxygen in reactions. At the end, the role of NAD(P)H quinone oxidoreductase (NQO1) was evaluated on these compounds, showing their intrinsic activity in the mecanism ofaction of these compounds.